Rotational molding technology - Crawford, R. J. (Roy James), 1949- (Plastics Design Library., 2002)
This book clarifies and quantifies many of the technical interactions in the process. It distinguishes itself from other books on the subject by being a seamless story of the advanced aspects of the rotational molding process. There are seven chapters within the book. The US market for rotational molding products was one billion pounds in the year 2000. The growth of the rotational molding industry has grown at 10 to 15% per year. With this growth has come an increasing need for details on the complex, technical aspects of the process.